1981
DOI: 10.1007/bf00917858
|View full text |Cite
|
Sign up to set email alerts
|

Toward an empirical subclassification of ?learning disabilities?: A psychophysiological comparison of ?hyperactive? and ?nonhyperactive? subgroups

Abstract: The diagnostic category of learning disabilities is a heterogeneous one, but few empirical attempts have been made to distinguish subgroups. Recent research, however, suggests that it may be meaningful to discriminate between "hyperactive" and "nonhyperactive" learning-disabled children. In the present study, 21 learning-disabled children identified as "hyperactive" through teacher nominations and ratings were compared to 15 learning-disabled children identified as "nonhyperactive" in the same manner. The two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1983
1983
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…Each of these approaches to defining an RD group implicitly assumes that RD is a relatively homogeneous disorder, at least in terms of its phenotypic presentation. Yet, current research, as well as a perusal of studies identifying children with RD, supports the notion of RD as a heterogeneous disorder (Anderson, 1992;Delamater, Lahey, & Drake, 1981; Doehring & Hoshko, 1977;Finucci, Isaacs, Whitehouse, & Childs, 1983;Flynn & Deering, 1989;Korhonen, 1991;Lubs et al, 1988;Njiokiktjien, 1994;Smith, Pennington, Kimberling, & Ing, 1990) comprising subgroups of children characterized by different patterns of cognitive and information processing.…”
supporting
confidence: 60%
“…Each of these approaches to defining an RD group implicitly assumes that RD is a relatively homogeneous disorder, at least in terms of its phenotypic presentation. Yet, current research, as well as a perusal of studies identifying children with RD, supports the notion of RD as a heterogeneous disorder (Anderson, 1992;Delamater, Lahey, & Drake, 1981; Doehring & Hoshko, 1977;Finucci, Isaacs, Whitehouse, & Childs, 1983;Flynn & Deering, 1989;Korhonen, 1991;Lubs et al, 1988;Njiokiktjien, 1994;Smith, Pennington, Kimberling, & Ing, 1990) comprising subgroups of children characterized by different patterns of cognitive and information processing.…”
supporting
confidence: 60%
“…There are few studies concerned with differences between hyperactive and nonhyperactive subgroups of learning-disabled children (but see Lahey & Drake, 1981;Dykman, Walls, Suzuki, Ackerman & Peters, 1970) and it remains open whether differences found between hyperactives and controls in attentional processes are influenced by the presence of LDs within the hyperactive samples studied.…”
Section: Experiments 3: Sustained Selective Attention In Learning Disamentioning
confidence: 99%
“…Previous findings from autonomic stimulation studies have produced contradictory results for ADHD subjects. Although in some of these studies subjects with ADHD had a tendency to show lower autonomic stimulation either during rest or during cognitive or stress tasks (17,(30)(31)(32)(33)(34), other studies found there were children with ADHD who didn't present decreased autonomic stimulation (35,36). The authors tried to explain the reason of this contradiction as a result of not taking into account comorbidities like ODD and conduct disorder.…”
Section: Discussionmentioning
confidence: 99%